Critical Synthesis Package: Schwartz Value Survey (SVS) - Rashmi Kusurkar; Gerda Croiset (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Schwartz Value Survey (SVS), and (2) copies of the SVS instrument and scoring key developed by Shalom H. Schwartz, PhD. SVS is a self-report questionnaire developed for assessing individual differences in values, with values being defined as desirable, trans-situational goals, varying in importance, that serve as guiding principles in people's lives. SVS has 57 items grouped into 11 subscales: Conformity, Tradition, Benevolence, Universalism, Self-Direction, Stimulation, Hedonism, Achievement, Power, Security, and Spirituality. A responder indicates how important each value is for him/her as a guiding principle in his/her life on a 9-point Likert-type scale (−1 = opposed to my values, 7 = of extreme importance). The survey appears to have moderate reliability and good construct, content, and concurrent validity. It has also been validated across 47 languages. Although the survey has been used in health professions, it has been used less frequently in health professions education. In this context the survey offers several potential uses for researchers and educators, as measuring the values of health professions students could provide valuable information to advisors on how to guide their students towards the development of the appropriate attitudes and behaviors.